TEMPUS, a Timepix4-based system for the event-based detection of X-rays - Correa, Jonathan; Ignatenko, Alexandr; Pennicard, David; Lange, Sabine; Fridman, Sergei; Karl, Sebastian; Lohse, Leon; Senfftleben, Björn; Sergeev, Ilya; Velten, Sven; Prajapat, Deepak; Bocklage, Lars; et al. (Journal of Synchrotron Radiation, 2024)
TEMPUS is a new detector system being developed for photon science. It is based on the Timepix4 chip and, thus, it can be operated in two distinct modes: a photon-counting mode, which allows for conventional full-frame readout at rates up to 40 kfps; and an event-driven time-stamping mode, which allows excellent time resolution in the nanosecond regime in measurements with moderate X-ray flux. In this paper, the initial prototype, a single-chip device, is introduced, and the readout system described. Moreover, and in order to evaluate its capabilities, some tests were performed at PETRA III and ESRF for which results are also presented.<br
Keywords: X-ray detector; photon science; event-driven; sparse-readout; Timepix4.